1976
DOI: 10.1093/nar/3.4.953
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of single stranded DNA related to the transcriptional activity of animal cells

Abstract: Single stranded DNA (s.s.DNA) comprising 1-2% of the total nuclear DNA was isolated by an improved method of hydroxyapatite chromatography from native nuclear DNA3 of embryonic chick cells, labeled for several cell generations with 3H-thymidine. Small quantities of 3H-DNA were annealed with a large excess of unlabeled DNA or polysomal RNA from chick embryos. Hybridization kinetics (monitored by the use of SI nuclease digestion, hydroxyapatite chromatography and thermalfusion), indicated that s.s.DNA belongs to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

1977
1977
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…We recently obtained evidence that suggested other mechanisms might be involved. The "major part of ss-DNA could not consist of replication intermediates because its lifespan was similar to that of bulk DNA (10,33). Another possibility that had to be considered is that ss-DNA is related to RNA synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently obtained evidence that suggested other mechanisms might be involved. The "major part of ss-DNA could not consist of replication intermediates because its lifespan was similar to that of bulk DNA (10,33). Another possibility that had to be considered is that ss-DNA is related to RNA synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…We have isolated, from the nDNA of various species, a minor fraction of single-stranded DNA (ss-DNA) and demonstrated that about one-third of the ss-DNA from cultured normal embryonic chicken cells (10) or human RD cells (11) Isolation of ss-DNA. The modification of the method for hydroxyapatite chromatography used in these studies has been described (15 of the native nuclear DNA from leukemic chicken cells was isolated as ss-DNA.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…DNA, playing critical roles in storage and translation of genetic information [1][2][3][4], is an important target in drug discovery, especially in antiviral, anticancer and antibiotic drugs [5,6]. The study on the ligand-DNA-binding events is of great importance in rational design of novel drugs [7].…”
Section: Introductionmentioning
confidence: 99%
“…The method utilized to prepare RNA from the cytoplasmic phase of cells at 3 days (myoblasts: stage I), and 9 days (myotubes: stage IV) was previously reported [4]. In brief, after two successive centrifugations, 15 min at 5000 rev./min and 30 min at 12000 rev./min in a Sorvall swinging rotor, the final supernatant was made 0.2 M in MgClz and kept overnight at 4 "C. The precipitated RNA was pelleted and solubilized in 0.15 M NaCl, 0.01 M Tris-HC1 pH 7.4, 0.002 M EDTA.…”
Section: Preparation Of Cytoplasmic Rhtasmentioning
confidence: 99%